2005
DOI: 10.1136/ard.2003.019695
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of polymorphisms in the apolipoprotein AI-CIII-AIV cluster to hyperlipidaemia in patients with gout

Abstract: Background: Studies have shown that hyperuricaemia is independently related to the insulin resistance syndrome and that polymorphisms of the apolipoprotein AI-CIII-AIV cluster are also related to insulin resistance. Objective: To study the prevalence of polymorphisms of the apolipoprotein AI-CIII-AIV cluster in persons with gout and to determine whether these polymorphisms contribute to the pathophysiology of gout or to altered lipid concentrations. Methods: Plasma cholesterol, triglycerides, uric acid, VLDL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…According to the current study's data, hyperuricemia and hypertriglyceridemia are positively associated with each other. This relationship is still not totally clear in the literature, but there is purportedly a reduced renal excretion of uric acid in individuals with hyperuricemia and dyslipidemia 41 . Other studies have also shown a positive association between hypertriglyceridemia and hyperuricemia 37,38,39,41 .…”
Section: Discussionmentioning
confidence: 96%
“…According to the current study's data, hyperuricemia and hypertriglyceridemia are positively associated with each other. This relationship is still not totally clear in the literature, but there is purportedly a reduced renal excretion of uric acid in individuals with hyperuricemia and dyslipidemia 41 . Other studies have also shown a positive association between hypertriglyceridemia and hyperuricemia 37,38,39,41 .…”
Section: Discussionmentioning
confidence: 96%
“…For reports with multiple risk estimates (for a single outcome), the results cited in the original systematic review were extracted and their corresponding properties were assessed (combination of variables in the statistical model, exposure definition, etc.). Two study reports in the form of abstracts [ 21 , 22 ] were excluded, as they did not contain enough information to be assessed by the instrument. This left 37 articles to be evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that orally feeding animals with LE for a period of time can raise their cholesterol, increase production of low density lipoprotein cholesterol (LDL-C) and promote the de novo synthesis of purine nucleotide from ribose 5-phosphate to 5-phosphoribosyl pyrophosphate via the common metabolic pathway of NADP-NADPH. This will eventually lead to increased generation of uric acid while its excretion is decreased [ 27 , 28 ]. Another study found that high cholesterol levels can also cause oxidative stress, and oxidative stress can promote the feed-forward loop of uric acid production, which ultimately leads to elevated serum uric acid levels [ 29 ].…”
Section: Introductionmentioning
confidence: 99%